The Mode of Action of Heparin in Plasma - Béguin, Suzette; Lindhout, Theo; Hemker, H Coenraad (Thrombosis and Haemostasis, 1988)
The influence of heparin on prothrombin conversion in plasma was estimated by measuring prothrombin disappearance with the aid of staphylocoagulase or by calculation from the thrombin generation curve, compensating for simultaneous thrombin inactivation by plasma protease inhibitors. In thromboplastin-activated plasma the effect of heparin on prothrombinase (factor Xa-factor Va-phospholipid) is negligible compared to that on thrombin probably because both the extrinsic factor X activating complex and phospholipid bound factor Xa are insensitive to AT III-heparin action. In contact-activated plasma prothrombinase generation is inhibited by heparin, because heparin lowers the ambient concentrations of thrombin so that the feedback activation of factor VIII by thrombin is diminished. Consequently, the delayed factor Xa generation causes a lag phase in prothrombinase generation. We conclude that heparin in plasma acts by its thrombin scavenging properties. No direct action on prothrombinase or on the factor X activating enzyme needs to be assumed if one takes into account the effect of thrombin depletion on thrombin-mediated feedback reactions
Keywords: Prothrombin activation; Heparin; Plasma protease inhibitors